Stencil-printed electrodes without current collectors and inactive additives on textiles for in-plane microsupercapacitors. Issue 44 (3rd November 2021) - Xie, Xudong; Guo, Ruisheng; Yang, Bingjun; Li, Haodong; Yang, Fangshe; Shen, Baoshou
Abstract : Flexible and wearable in-plane micro-supercapacitors (MSCs) are fabricated by one-step stencil printing electrode materials on textiles. The printed electrode can be the current collector and active material simultaneously. Abstract : Textile-based energy storage devices are exceedingly finding requirements in the development of wearable and intelligent electronics, which need the energy to be supplied to forms such as flexible sensors and displays. In-plane microsupercapacitors (IMSCs) with patterned electrodes have attracted much attention due to their high power-density, fast charging-discharging, long cycle-life, free maintenance, and easy integration with other devices. For printing patterns, stencil printing technology is a scalable and compatible method with textiles. However, present methods need extra conducting current collectors fabricated by sewing, printing, or laser scribing techniques. Meanwhile, the active materials need further treatment. To simplify the fabrication procedure, a new strategy about a one-step printing electrode pattern is put forward without extra metal current collectors and inactive additives. Based on water-dispersible properties, poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) as the conductive and active material simultaneously, conductive carbon skeleton with porosity and one-dimensional carbon nanotubes are mixed to formulate the paste. The paste shows excellent printability on rough and porous textiles. The fabricated textile IMSCs display higher energy and power density than other textile IMSCs with one-step printed electrodes. Moreover, these IMSCs exhibit outstanding flexibility, integrated capability, and practical wearability. These demonstrations hold great promise in the forthcoming wearable electronics era as an effective textile energy device.